The Politics of Ethics / Methods for Acting, Learning, and sometimes Fighting with Others in Addressing Ethics Problems in Organizational Life - Nielsen Richard P (Oxford University Press, 1996)
This book analyzes the individual, organizational, cultural, and environmental obstacles to behaving ethically in organizations. Introduction, Obstacles to Ethical Organization Behavior, A Politics of Ethics Framework Based on Action-Learning, Single-Loop and Win-Lose Methods, Double-Loop and Dialog Methods, Friendly Disentangling: Triple-Loop Dialog I, Friendly Upbuilding: Triple-Loop Dialog II, Varieties of Postmodernism: Triple-Loop Dialog III, Internal Due-Process Systems: Ethics Processing Machines, Single and Double and Triple - Loop Politics: Overcoming Obstacles to Ethical Organization Behavior, Conclusion: Proteus as Organization Citizen, Appendix: Varieties of Dialectic Change Processes, References, Index.